Crack Formation on Resected Root Surfaces Subjected to Conventional, Ultrasonic, and Laser Root-End Cavity Preparation - MUMCU, GONCA; KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (MARY ANN LIEBERT, INC, 2014)
Objective: The aim of this study was to evaluate cracks on root ends following resection and cavity preparation with a laser and two established techniques. Background data: If root canal treatment of a tooth fails, an apicoectomy operation may be indicated. Three millimeters of the root tip is resected and a cavity of similar depth with parallel walls is cut to receive a root-end filling. Materials and methods: Sixty extracted human maxillary anterior teeth were used. Their root canals were prepared with rotary instruments, and they were filled with gutta-percha. Twenty teeth were resected with tungsten carbide fissure burs, and their root-end cavities cut with tungsten carbide round burs at a slow speed (Group 1). The other 40 teeth were resected with an Er:YAG laser, and root-end cavities were made with the same laser (Group 2), or with an ultrasonically-powered zirconium nitride coated retrotip (Group 3). The number and types of cracks on the resected surfaces were assessed using a stereomicroscope before and after cavity preparation. Results: Cracking was not significantly different between the more conventional group and the laser groups after resections (p > 0.05) or following cavity preparation (p > 0.05). Conclusions: In this in vitro study, the laser resection and root-end preparation technique did not influence the number or type of cracks formed on the root surfaces.
Keywords: ELECTRON-MICROSCOPIC EVALUATION; DENTAL HARD SUBSTANCES; ER YAG LASER; IN-VITRO; TEETH; INTEGRITY; SURGERY; ERBIUM; APICES